2005
DOI: 10.1007/s00395-005-0567-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acids increase expression of GLUT4 in dedifferentiated and hypertrophied cardiac myocytes

Abstract: Sufficient expression of the insulin-sensitive glucose transporter GLUT4 may be crucial for the survival of cardiac myocytes in situations of stress. Expression of GLUT4 in cardiac myocytes correlates with cell differentiation and is reduced in the hypertrophied and failing myocardium. Adult rat cardiomyocytes (ARC) in primary culture undergo dedifferentiation and reduction of GLUT4 expression. Depending on the culture condition partial redifferentiation and/or hypertrophy follows. All-trans (at) and 9-cis ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
4
13
1
Order By: Relevance
“…It was therefore of interest to examine the interaction of ATRA with glucose metabolism in our skeletal muscle cell model. In good concordance with previous observations in cardiac myocytes [48], ATRA exposure increased the mRNA levels of the insulin-regulated glucose transporter GLUT4 in C2C12 skeletal myocytes. However, GLUT4 mRNA levels only indirectly reflect glucose uptake capacity, as this is primarily regulated by transport of GLUT4 to the plasma membrane, and in fact in our hands basal and insulin-stimulated 2-DOG uptake in C2C12 myocytes were unaffected by ATRA treatment.…”
Section: Discussionsupporting
confidence: 80%
“…It was therefore of interest to examine the interaction of ATRA with glucose metabolism in our skeletal muscle cell model. In good concordance with previous observations in cardiac myocytes [48], ATRA exposure increased the mRNA levels of the insulin-regulated glucose transporter GLUT4 in C2C12 skeletal myocytes. However, GLUT4 mRNA levels only indirectly reflect glucose uptake capacity, as this is primarily regulated by transport of GLUT4 to the plasma membrane, and in fact in our hands basal and insulin-stimulated 2-DOG uptake in C2C12 myocytes were unaffected by ATRA treatment.…”
Section: Discussionsupporting
confidence: 80%
“…Although our previous experiments suggested that the development of insulin resistance in vitro was independent of GLUT4 expression (19), we determined whether changes in GLUT4 expression in response to nuclear receptor agonists could contribute to the improved insulin responsiveness. Similar to published observations (33,39), GLUT4 expression was reduced after 3 d in culture but slightly enhanced in the presence of 9-cis RA or TTNPB (Fig. 7).…”
Section: Expression Of Glucose Transporterssupporting
confidence: 91%
“…Adult rat cardiac myocytes were isolated as described previously (39) and cultured in M199 medium (Sigma-Aldrich) supplemented with 20 mM creatine, 100 M cytosine-␤-D-arabinofuranoside, 20% FCS, and 10 Ϫ7 M 9-cis retinoic acid to improve cardiac myocyte differentiation (38) and prevent transient insulin resistance (39). All additions to this basal medium were present at the time of plating (day 0) and for the entire length of the culture.…”
Section: Animalsmentioning
confidence: 99%